Traces of Local Language in Lembak Ethnic Folktales: Inventory and Documentation as a Medium of Cultural Literacy - Agung Nugroho; Inda Puspita Sari; Cekman; Houtman (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
Folklore is an important medium for preserving regional languages and transmitting cultural values to the community. However, most Lembak ethnic folklore has not been systematically documented, thus facing the potential for extinction as the number of speakers of the local language decreases. This study aims to identify the uniqueness of the language, document the folklore, and uncover the cultural values contained in Lembak ethnic folklore as a medium for local cultural literacy. This study uses a qualitative approach with vocabulary and linguistic element inventory methods, story documentation through transcription and transliteration processes, and content analysis to examine the cultural values contained in the story texts. The results show that the Lembak language has distinctive phonological, morphological, and syntactic characteristics, which are reflected in vocabulary, traditional expressions, and sentence patterns that represent the community's oral traditions. The documentation of the folklore also successfully captures local history, community cosmology, heroic values, and traditional beliefs as part of Lembak cultural identity. The content analysis reveals the existence of moral, social, religious values, and local wisdom that are relevant to strengthening character education. Thus, Lembak ethnic folklore has the potential to become an effective local cultural literacy medium to support the preservation of regional languages, strengthen cultural identity, and become a source of contextual learning in educational environments.   Cerita rakyat merupakan salah satu media penting dalam pelestarian bahasa daerah dan transmisi nilai budaya kepada masyarakat. Namun, sebagian besar cerita rakyat etnik Lembak belum terdokumentasi secara sistematis sehingga berpotensi mengalami kepunahan seiring berkurangnya penutur bahasa daerah. Penelitian ini bertujuan untuk mengidentifikasi kekhasan bahasa, mendokumentasikan cerita rakyat, serta mengungkap nilai-nilai budaya yang terkandung dalam cerita rakyat etnik Lembak sebagai media literasi budaya lokal. Penelitian ini menggunakan pendekatan kualitatif dengan metode inventarisasi kosakata dan unsur linguistik, dokumentasi cerita melalui proses transkripsi dan transliterasi, serta analisis isi untuk mengkaji nilai budaya yang terdapat dalam teks cerita. Hasil penelitian menunjukkan bahwa bahasa Lembak memiliki karakteristik fonologis, morfologis, dan sintaktis yang khas, yang tercermin dalam kosakata, ungkapan tradisional, dan pola kalimat yang merepresentasikan tradisi tutur masyarakat. Dokumentasi cerita rakyat juga berhasil merekam sejarah lokal, kosmologi masyarakat, nilai kepahlawanan, serta kepercayaan tradisional sebagai bagian dari identitas budaya Lembak. Analisis isi mengungkap adanya nilai moral, sosial, religius, dan kearifan lokal yang relevan dengan penguatan pendidikan karakter. Dengan demikian, cerita rakyat etnik Lembak berpotensi menjadi media literasi budaya lokal yang efektif untuk mendukung pelestarian bahasa daerah, memperkuat identitas budaya, serta menjadi sumber pembelajaran kontekstual di lingkungan pendidikan.